Combination effect of 4-picolinic acid with 5A zeolite on ammonium polyphosphate flame-retarded sawdust board. (May 2014) - Yuan, Liping; Chen, Xun; Hu, Yunchu
The flammability and thermal stability of ammonium polyphosphate–treated flame-retarded sawdust boards were compared with those also containing 5A zeolite and 5A zeolite that had been impregnated with 4-picolinic acid. This comprehensive study was performed using cone calorimetry, thermogravimetric analysis and scanning electron microscopy. The results demonstrated that acid-treated 5A zeolite, which was incorporated into ammonium polyphosphate–based flame-retardant systems, showed superior performance to ammonium polyphosphate being used alone. This was determined by comparing the peak heat release rate, total heat release, fire growth index, smoke release rate, and total smoke emission. The thermogravimetric analysis results showed that 4-picolinic acid significantly altered the thermal stability of ammonium polyphosphate, which was catalytically decomposed in advance so as to retard combustion. Digital photography and scanning electron microscopy observations showed that 5A zeolite used with 4-picolinic acid efficiently promoted the formation of a continuous and consolidated charred layer.